Influence of alkyne spacers on the performance of thiophene-based donors in bulk-heterojunction organic photovoltaic cells. (April 2021) - Marques dos Santos, John; Neophytou, Marios; Wiles, Alan; Howells, Calvyn Travis; Ashraf, Raja Shahid; McCulloch, Iain; Cooke, Graeme
Abstract: The ever-increasing demand for renewable energy has led to the intensification of research focused upon harnessing the abundant energy from sunlight. Solution processed organic solar cells fabricated using conjugated polymer donor materials dominated the early development of organic photovoltaics (OPV). More recently, organic solar cells fabricated using small molecule donors have become increasingly attractive due to the advantages these systems have over their polymeric counterparts. These include reproducible synthesis and the ability to more accurately develop structure-activity relationships. Here, we report the synthesis of thiophene based small molecule donors that have been used to investigate the influence of alkyne π-spacers on the optical, electronic and photovoltaic properties of solution-processable bulk-heterojunction (BHJ) organic OPV cells. Additionally, we compare the addition of 3, 4-ethylenedioxythiophene (EDOT) units in place of the end-thiophene of these derivatives. We found that the compounds featuring alkyne moieties displayed poor charge transfer and blue-shifted UV–vis spectra, whereas the incorporation of the EDOT units increased charge transfer for the non-alkyne derivative resulting in red-shifted absorbance. DFT calculations predicted higher charge separation/mobility and lower charge generation for the compounds without alkyne units. Indeed, greater Jsc values and higher PCEs were found for the compounds lacking alkyne spacers. EDOT containing compounds showed poor performance which is likely due to an unfavourable morphology and higher HOMO level, leading to lower Voc . Hence, the simplest 5T-1 molecule showed the highest performance of 3.24%, which is c.a. 1.6x that of the alkyne-containing 5TA-1 and c.a. 2.9x that of the EDOT-containing derivative. This study demonstrates that alkyne spacers can be detrimental to orbital interactions, charge transfer and OPV performance, and that the EDOT unit can be added to provide greater charge transfer due to its auxiliary donating ability. However, careful design is required to ensure higher Voc values and a favourable morphology in thiophene-based solution-processable OPVs. Highlights: The role alkynes play in the photophysics and OPV performance of a series of thiophene-based dyes is investigated. Alkyne-containing compounds show poorer CT and blue-shifted UV-vis spectra. Alkyne-free compounds show the highest device performances. EDOT moieties provide greater CT, however, they lead to unfavourable morphology.